Uma proposta de UEPS para a construção dos conceitos físicos relacionados à hidrostática no ensino médio - Gonçalves, Sheila Borges (2022)
This work is an action research through which was proposed a Teaching Unit Potentially Significant used for application in 1st grade high school classes on the occasion of the presentation of Hydrostatic concepts. It is observed that many of the situations addressed in hydrostatics are common to everyday life of most students, especially in a coastal state like Espírito Santo. As it happens in mechanics and electricity, students have difficulty abandoning their spontaneous conceptions regarding the subject. Given this scenario and the scarcity of work with this theme was proposed in this work, the development of a Teaching Unit Potentially Significant to teach Hydrostatic and that used different materials and teaching strategies. As a theoretical reference, it was used the Ausubel's Theory of Meaningful Learning and Moreira's guidelines for the development of a UEPS. The work was divided into three stages, totaling 11 classes of 50 minutes. In the first stage of the work, a diagnostic test was applied. From the results obtained in the pre-test it was verified the need for adequacy/adaptation of the instructional materials. It was decided to develop a series of classes in which it was possible to correct observed difficulties and, at the same time, introduce physical concepts related to Hydrostatics. In classes 2 to 10 the contents of Hydrostatics were developed: pressure, atmospheric pressure, density, Stevin's theorem, communicating vessels, Pascal's principle, hydraulic press, buoyancy and Archimedes' theorem. For this, it was used demonstrative and collaborative experiments, computer simulation, videos, exercises and a didactic game. In the last stage a post-test was applied, consisting of questions similar to the pre-test, but with a higher level of depth. The comparison between the pre and post-test results provided indications about the influence of the developed and applied instructional material.